Heat transfer of staggered bundles of flat oval tubes in transverse flow - Кондратюк, Вадим Анатолійович; Терех, Олександр Михайлович; Баранюк, Олександр Володимирович; Письменний, Євген Миколайович (Eastern-European Journal of Enterprise Technologies, 2015)
The paper deals with investigating convective heat transfer for virtually unstudied staggered bundles of flat-oval tubes at their transverse air flow around. Experiments were conducted in an open-circuit wind tunnel with rectangular cross-section in the range of Reynolds numbers change from 2000 to 30000. In the course of experiments, the average convective heat transfer coefficients were determined. When processing and analyzing experimental data and dependencies of Nusselt numbers on Reynolds numbers of bundles of flat-oval tubes, much attention was paid to factors, which may affect the heat transfer intensity. During the experiments, several of these factors: operation factor - flow rate W, geometrical factors: back pitch between tubes S1, long pitch S2, the ratio of longitudinal to transverse tube size (profile elongation) d2/d1 were identified.